Long-Term Neurodevelopmental Outcomes Following Early Hormonal Intervention in Congenital Hypothyroidism: A Randomized Controlled Follow-Up Study in Pakistan. - Anam Amjad Buttar, Muhammad Saeed, Jazib Andleeb, Sardar Ahmad, Sana Ashraf, Khadija Kiran, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Congenital hypothyroidism is a preventable cause of long-term neurodevelopmentalimpairment, yet optimal timing and dosing of early hormonal replacement remain debated. This randomized controlled follow-up study